AN EXPLORATORY STUDY OF ENGLISH SYNTAX: PARTS OF SPEECH, PHRASE STRUCTURE, AND SENTENCE CONSTRUCTION - Enzelly Hernita Sidabalok; Sintya Margaretha Sinaga; Rentina Flora Indah Ompusunggu; Cindy Debora Manurung (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Syntax plays a foundational role in understanding the structure of language, particularly in the context of English language learning. This paper explores the classification of English parts of speech, their syntactic roles, phrase composition, and sentence structures. Drawing upon both classical syntactic frameworks and recent linguistic scholarship (2015–2025), the study analyzes how word categories function and interact within phrases and clauses. Special attention is paid to the pedagogical implications of syntactic awareness for EFL learners, linking theory with practical application. By revisiting concepts introduced by Hambali & Mirizon (2017) and expanding them with insights from contemporary linguistics, this paper provides a comprehensive overview of English syntax relevant to both educators and learners.